How can the co-production of knowledge contribute to food system transformation? - Nehring, Ryan; Rodriguez, Fernando Galeana; Faxon, Hilary (CGIAR, 2023)
“Co-production,” “co-creation,” “co-development,” “co-design,” and similar terms have become common in research-for-development projects. These terms also appear in approaches taken by the European Union and the U.S. Agency for International Development, among others. In food systems and environmental sustainability, academics and policymakers are applying knowledge co-production as a method of participatory research. Evidence shows co-creation and trust matter for policymaking, yet implementing such approaches is not easy, demanding resources, expertise, and care. More fundamentally, co-production is often used to indicate people coming together – to learn, exchange experiences, and generate new ways of knowing and doing – without adequate consideration of the power relations in these knowledge systems.